Emergency and Trauma of the Elbow - Bazzocchi, Alberto; Gómez, Maria Pilar Aparisi; Bartoloni, Alessandra; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2017)
The elbow is a joint composed of three different articulations all included in the same synovial capsule, with a complex anatomy that allows two kinds of motion: flexion-extension and pronation and supination. Stabilization of the elbow is provided by osseous and ligamentous structures.When assessing the elbow in the traumatic setting, the mechanism of injury determines the pattern of osseous and ligamentous lesion, with potential important implications on elbow instability. The role of the radiologist in the assessment of the traumatic elbow requires an understanding of the most common injury mechanisms in traumatic elbow injuries. This knowledge facilitates the detection of potential secondary occult bone and soft tissue injuries that could lead to chronic instability.We analyze the acute patterns of injury of the osseous, ligamentous, musculotendinous, and neurovascular structures, with a focus on the most commonly used classifications of fractures and fracture-dislocations. We also discuss the therapeutic management of these injuries, with mention of the most frequently used surgical techniques and the commonly expected posttreatment findings.Finally, we review the repetitive microtrauma patterns of injury of the elbow joint structures and the most common pitfalls in the interpretation of elbow imaging.
Keywords: elbow trauma; elbow injuries; X-ray; CT; MRI